2022
DOI: 10.1097/qco.0000000000000861
|View full text |Cite
|
Sign up to set email alerts
|

Duration of antibiotic therapy in Gram-negative infections with a particular focus on multidrug-resistant pathogens

Abstract: Purpose of reviewAntimicrobial overuse is a major health problem that contributes to antimicrobial resistance (AMR). Infections with Gram-negative bacilli (GNB) and multidrug-resistant organisms (MDRs) are associated with high morbidity and mortality, particularly in patients with underlying medical conditions. Recent findingsAlthough many recent studies have been published about the novel antibiotics in treating infections including those due to MDR-GNB, the optimal duration of treatment (DOT) remains inconcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…While many studies have supported the use of shorter antimicrobial courses to decrease AMR, cost, and adverse effects [ 117 ], the evidence on shortening the duration of treatment for a pseudomonal infection remains inconclusive. The duration of treatment for P. aeruginosa severe sepsis should be individualized according to the primary site of infection, the patient’s risk factors and underlying comorbidities, source control, susceptibility testing, trends of inflammatory biomarkers, and clinical improvement [ 118 ]. A recently published retrospective study comparing a short (6–10 days) course of antibiotics to a longer (11–15 days) course for P. aeruginosa bacteremia found no difference in mortality or bacteremia recurrence but found a significantly reduced hospitalization duration with shorter duration of treatment [ 119 ].…”
Section: Key Factors Related To Therapymentioning
confidence: 99%
“…While many studies have supported the use of shorter antimicrobial courses to decrease AMR, cost, and adverse effects [ 117 ], the evidence on shortening the duration of treatment for a pseudomonal infection remains inconclusive. The duration of treatment for P. aeruginosa severe sepsis should be individualized according to the primary site of infection, the patient’s risk factors and underlying comorbidities, source control, susceptibility testing, trends of inflammatory biomarkers, and clinical improvement [ 118 ]. A recently published retrospective study comparing a short (6–10 days) course of antibiotics to a longer (11–15 days) course for P. aeruginosa bacteremia found no difference in mortality or bacteremia recurrence but found a significantly reduced hospitalization duration with shorter duration of treatment [ 119 ].…”
Section: Key Factors Related To Therapymentioning
confidence: 99%
“…To the best of our knowledge, no existing study has reported long-term antimicrobial therapy as a risk factor for the development of resistant organisms in patients with AC. However, a relationship between long-term antimicrobial therapy and the development of resistant organisms was reported in patients with other infectious diseases 16 17 32 . Therefore, we investigated the factors involved in the development of resistant organisms in patients with recurrent cholangitis, including long-term antimicrobial therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Controlling duration of therapy is among the most important pillars of antimicrobial stewardship. As the evidence accumulates against long duration of treatment, most guidelines have moved towards recommending shorter duration of therapy for various infections particularly for Gram-negative pathogens (81). However, little to no data is available about the efficacy of a shorter duration of treatment for PVE.…”
Section: Duration Of Therapymentioning
confidence: 99%